Popular sovereignty in the West : polities, contention, and ideas - Nootens, Geneviève. (Routledge innovations in political theory ;, 2013)
"This book is an inquiry into the history of the idea of popular sovereignty as it has been shaped by the struggles between rulers and ruled. It builds on the notion that a thorough analysis of how the idea of popular sovereignty emerges from, and interacts with, a political history of contention within changing polities can help us to draw similarities and differences with our own age. Providing a historical perspective to the present day, Nootens pays strong attention to the role of democratization processes and to the relationship between meanings conveyed by the idea of popular sovereignty, political contention, and changing representations of the governing relationship. The latter has been undergoing significant transformations in the last decades, and these transformations impact significantly upon people's rights, interests, wealth, and capacity to decide for themselves. In order to understand popular sovereignty in an era of globalization, this book argues that focus should be put on current struggles between rulers and ruled, as well as on current transformations of the relationship between public and private spheres. Understanding the claims involved in current processes of contention over decision-making processes is key to understanding popular sovereignty in an era of globalization.Making an important contribution to debates on sovereignty, Popular Sovereignty in the West will be of interest to students and scholars of modern political theory, sovereignty, and democratization studies"--